2017
DOI: 10.1016/j.tust.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Ultimate capacity of a segmental grey cast iron tunnel lining ring subjected to large deformations

Abstract: Understanding t he behaviour of existing tunnels subjected to in - service deformations, as a result of the construction of underground works (e.g. new tunnel s ) in their proximity, is of importance in order to safeguard infrastructure within the u r ban environment. The associated deformations that t ake place during tunnelling have to be carefully assessed and their impact on the existing tunnels need s to be considered . A half - scale segment al grey cast iron (GCI) tunnel lining ring was tested as part o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…However, their stiffnesses depend on some factors, such as the geometrical configuration, properties of gasket and bolt, and internal forces direction of joints. Model tests are considered to be the most reliable approach to obtain the joint stiffness and have been widely used and reported in literature . Herein, the sign convention is as illustrated in Figure , in which the directions of the arrows signify the positive.…”
Section: Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their stiffnesses depend on some factors, such as the geometrical configuration, properties of gasket and bolt, and internal forces direction of joints. Model tests are considered to be the most reliable approach to obtain the joint stiffness and have been widely used and reported in literature . Herein, the sign convention is as illustrated in Figure , in which the directions of the arrows signify the positive.…”
Section: Formulationmentioning
confidence: 99%
“…Model tests are considered to be the most reliable approach to obtain the joint stiffness and have been widely used and reported in literature. 22,23,27,29,[33][34][35] Herein, the sign convention is as illustrated in Figure 2, in which the directions of the arrows signify the positive. Based on the test results reported in the literature, Lee et al 14 found that the rational joint stiffness k φ depended on the direction of the bending moment and that the rotational stiffness when a joint is subjected to a negative bending moment (denoted by k φ− ) is only 1/3~1/2 of that when a joint is subjected to a positive bending moment (denoted by k φ+ ).…”
Section: Internal Force Direction Dependent Of Joint Stiffnessmentioning
confidence: 99%
“…One of the objectives of the overall project was to study the behaviour of grey cast iron (GCI) tunnel linings. To this end, experimental tests were performed on a model tunnel lining (Yu et al, 2017, Afshan et al, 2017 which consisted of six segments bolted together to form a full ring with dimensions scaled to be 50% of those of the running tunnel linings of the Central Line in the LU network ( Figure 1). This was the smallest size that could be manufactured with GCI while maintaining true proportionality of all dimensions, particularly the skin of the segment.…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…The purpose of the FE analysis was not to merely reproduce the two-segment test but to provide insight into the behaviour of the joint under different boundary conditions. The ultimate aim of the FE analysis was to help establish the experimental setup for the model tunnel lining (Yu et al, 2017, Afshan et al, 2017. Therefore, the FE mesh employed in the analyses presented here forms part of the FE mesh adopted in the analysis of the full ring, consisting of six bolted GCI segments, as explained later.…”
Section: Purpose Of the Studymentioning
confidence: 99%
See 1 more Smart Citation